2022
DOI: 10.3389/fonc.2022.995639
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for patients with glioma: A recent scientometric analysis of the Web of Science in 2022

Abstract: BackgroundPatients with glioma present with complex palliative care needs throughout their disease trajectory. A scientometric analysis is effective and widely used to summarize the most influential studies within a certain field. We present the first scientometric analysis of palliative care for patients with glioma.MethodsBased on a Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) principle, we conducted a generalized search for articles on palliative care for glioma in the Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[68][69][70] Patients with advanced brain malignancies therefore have an increasing need for end-of-life care. Xiao et al 71 found through systematic analysis that there are multiple needs for end-of-life care for patients with advanced glioma, including physical, psychological, social and spiritual needs, and glioma patients should meet their personalized treatment needs, improve the quality of life of patients at the end of their lives, and reduce the family burden of patients. Koekkoek et al 69 reported that hospice care can reduce the pain of patients in the later stage of high-grade glioma patients, while improving the quality of life of patients in the later stage of life, and reducing the family burden of patients and their families.…”
Section: Hospice Care In Patients With Advanced Cancermentioning
confidence: 99%
“…[68][69][70] Patients with advanced brain malignancies therefore have an increasing need for end-of-life care. Xiao et al 71 found through systematic analysis that there are multiple needs for end-of-life care for patients with advanced glioma, including physical, psychological, social and spiritual needs, and glioma patients should meet their personalized treatment needs, improve the quality of life of patients at the end of their lives, and reduce the family burden of patients. Koekkoek et al 69 reported that hospice care can reduce the pain of patients in the later stage of high-grade glioma patients, while improving the quality of life of patients in the later stage of life, and reducing the family burden of patients and their families.…”
Section: Hospice Care In Patients With Advanced Cancermentioning
confidence: 99%
“…Glioma patients have a wide range of palliative care requirements, including requirements for physical, psychological, social, and spiritual support. Rehabilitation plays a very crucial role in the prevention of postoperative complications after any neurosurgery, like deep vein thrombosis and pressure sores due to prolonged bed rest, reduces the length of hospital stay, decreases time on ventilation, improves muscle strength, and increases independence in activities of daily living to improve functional capacity and quality of life [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%